The Effectiveness of Religious Approaches in Combating Juvenile Delinquency: A Case Study of Reading and Memorizing the Qur'an as a Form of Punishment - Dirman Dirman; Raehang Raehang; Marzuki Marzuki (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
This research discusses about giving punishment through reading and memorizing the Al-Qur'an as a strategy for dealing with juvenile delinquency. Juvenile delinquency is an increasingly disturbing issue in modern society, considering its negative impact on individual and social development. The aim of this research is to explore the effectiveness of implementing Al-Qur'an-based punishment in dealing with juvenile deviant behavior. The research method uses a qualitative approach with data collection techniques through observation, interviews and document analysis. The research results show that giving punishment through reading and memorizing the Al-Qur'an can have a positive impact on adolescent behavior. The Qur'an not only serves as a source of punishment, but also as a moral and spiritual guide, providing a deeper understanding of the values ​​of correct life. Applying punishment through reading and memorizing the Koran can also have long-term effects, because teenagers are not only given physical sanctions, but also the opportunity to reflect on their actions through understanding relevant verses of the Koran. Thus, this approach can be a potential alternative in tackling juvenile delinquency, creating a younger generation who is more responsible and has noble character. This research contributes to further understanding of the role of religion in shaping the character and behavior of adolescents and provides direction for related parties in developing juvenile delinquency prevention programs based on religious values.